Development and ultra‐structure of an ultra‐thin silicone epidermis of bioengineered alternative tissue - Wessels, Quenton (Int Wound J, 2013)
Burn wound care today has a primary objective of temporary or permanent wound closure. Commercially available engineered alternative tissues have become a valuable adjunct to the treatment of burn injuries. Their constituents can be biological, alloplastic or a combination of both. Here the authors describe the aspects of the development of a siloxane epidermis for a collagen‐glycosaminoglycan and for nylon‐based artificial skin replacement products. A method to fabricate an ultra‐thin epidermal equivalent is described. Pores, to allow the escape of wound exudate, were punched and a tri‐filament nylon mesh or collagen scaffold was imbedded and silicone polymerisation followed at 120°C for 5 minutes. The ultra‐structure of these bilaminates was assessed through scanning electron microscopy. An ultra‐thin biomedical grade siloxane film was reliably created through precision coating on a pre‐treated polyethylene terephthalate carrier.